2013
DOI: 10.1007/s10792-013-9891-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-fever retinitis: a single center experience from south India

Abstract: Various retinal manifestations can occur following a febrile illness due to viral, bacterial or protozoal etiology. As there are limited data in the literature, we undertook this study to analyse the clinical presentation of post-fever retinitis due to various etiologies, as well as its course and management. This was a retrospective study of 14 consecutive cases who presented to the Vitreo Retina Department of our hospital over a 1-year period between January 2010 and December 2010. All patients underwent det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 10 publications
0
57
1
Order By: Relevance
“…Any interpretation of these data will need to take the epidemiology of the related pathogen into account, with herpesviruses having a particular high prevalence. In these patients, retrobulbar optic neuritis, papillitis, neuroretinitis, and vasculitis may coexist or occur in isolation (Vishwanath et al, 2013). Accepting a likely reporting bias of first presentations, it seems that most cases are that of an isolated unilateral or bilateral optic neuritis.…”
Section: Infectious and Postinfectiousmentioning
confidence: 99%
“…Any interpretation of these data will need to take the epidemiology of the related pathogen into account, with herpesviruses having a particular high prevalence. In these patients, retrobulbar optic neuritis, papillitis, neuroretinitis, and vasculitis may coexist or occur in isolation (Vishwanath et al, 2013). Accepting a likely reporting bias of first presentations, it seems that most cases are that of an isolated unilateral or bilateral optic neuritis.…”
Section: Infectious and Postinfectiousmentioning
confidence: 99%
“…Post fever retinitis and vasculitis as an entity usually manifests between 2 and 4 weeks after the fever in immunocompetent patients, irrespective of etiology. [ 1 2 ] Patients typically present with diminution of vision that is sudden in onset and painless. Patients can have varied posterior segment manifestations, including focal and multifocal patches of retinitis which could be unilateral or bilateral, possible optic nerve involvement, serous detachment at the macula, macular edema and localized involvement of the retinal vessel in the form of beading of the vessel wall, tortuosity, and perivascular sheathing.…”
mentioning
confidence: 99%
“…Looking back at the evidence from various case series and anecdotal case reports in the literature,[ 1 2 3 4 5 6 7 ] it is evident that the morphological appearance of the disease remains the same, irrespective of the cause of the fever. These manifestations seem to be a result of an immune-mediated mechanism.…”
mentioning
confidence: 99%
“…It is usually accompanied by mild vitreitis, retinal hemorrhages, compromise of retinal vessels, and the presence of areas of retinal whitening in the posterior pole [48]. Funduscopy allows visualizing focal and multifocal patches of retinitis macular edema, serous detachment at the macula, and localized involvement of the retinal vessel [49]. It is described that retinitis caused by chikungunya fever can simulate herpetic and West Nile virus retinitis; thus the importance of anamnesis lies in the identification of systemic symptoms of chikungunya infection, making possible the differentiation to other etiologies [50,51].…”
Section: Retinitismentioning
confidence: 99%
“…A retrospective study showed 14 consecutive cases who presented to the Vitreo Retina Department of the Minto Ophthalmic Hospital; of them one patient was positive for IgM chikungunya; she had bilateral anterior non-granulomatous uveitis and retinitis with optic nerve involvement in one eye; the patient showed a favorable response to oral prednisolone; the dose was tapered based on clinical response over a period of 6 weeks improving from an average of 2/60 to 6/24 vision [49]. In a similar way, a case series that included nine chikungunya patients with ocular involvement found a benign course in the cases of iridocyclitis and episcleritis; they showed complete resolution, with preservation of vision, and patients that presented with retinitis showed gradual resolution over a period of 6 to 8 weeks with systemic acyclovir and the corticosteroids [8].…”
Section: Visual Prognosismentioning
confidence: 99%